Pour une autre historicité : la poésie brésilienne à partir des années 1970 - André Goldfeder; Fabio Roberto Lucas; Lucius Provase; Roberto Zular (Brésil(s), 2019)
This article analyzes several Brazilian poems and poets of the 1970s, 1980s, and 1990s in order to understand the different poetic strategies created in this period to respond to the specific challenges of presentist historicity (Hartog). The relation between poetry and history, poetic enunciation and its contexts, is transformed. The poem internalizes, intensifies, and mobilizes a perceived loss of discursive guarantee and the multiplicity of periods in time, triggering variations and modulations between different contexts and temporalities, as can be seen in poems by Haroldo de Campos, Paulo Leminski, Nuno Ramos and others.